Nove telekomunikacijske usluge - Mikec, Antun (Promet - Traffic&Transportation)
Strategic telecommunication development direction in Croatia has to be expected in three segments. The first relates to the achievement of the appropriate subscriber density of the basic telecommunication service – telephony (GTP), the second is in the modernization and application of new technologies of the telecommunication network (IDN, ISDN), and the third refers to the introduction of the wide range of new telecommunication services. Review and systematization of the telecommunication services is the main topics of the paper. A group of voice services and possibilities and non-voice services have been analyzed. In the paper there has also been discussed the problem of service integration from the exploitation viewpoint, technical and technological solutions as well as the commercial attractiveness. In it there has been given the review of the activities and the level of introduction of new services in HPT.